Regional Economic Policy Analysis: Problem Structuring and Forecasting Economic Growth in East Kalimantan - Perdana, Gusti Naufal Rizky; Hakim, Abdul; Suryadi, Suryadi (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
Economic development plays a crucial role in efforts to improve income and welfare for the community. However, East Kalimantan still faces various issues in its economic growth. Slow economic growth can be a hindrance to achieving development goals. Therefore, policy analysis on regional economic policies is essential. The aim of this research is to provide a detailed description and in-depth analysis of the existing problems of economic growth in East Kalimantan Province and to forecast the economic growth of East Kalimantan Province for the next five years, which will serve as the basis for strategic planning for the future of the region. This research is a qualitative descriptive study. Data sources were selected using purposive sampling techniques. Data collection techniques included observation, interviews, and documentation. The data analysis technique used is the interactive model from Miles et al., (2014), which consists of data reduction, data display, and conclusion drawing or verification. The results of the study indicate that East Kalimantan Province faces serious challenges in economic diversification and reducing dependence on the mining and quarrying sector. This situation poses long-term risks as natural resources are non-renewable. Serious efforts are needed to formulate policies that promote economic diversification to ensure economic sustainability. The economic growth forecast highlights the importance of careful strategies in optimizing the potential of the National Capital City relocation to support stable and sustainable economic growth in the future.